Elementary School Teachers’ Perceptions on English Teaching in Cirebon - Sri Hastuti (IAIN Syekh Nurjati Cirebon, 2021)
In 2013 Curriculum, English is not explicitly mentioned as one of the subjects at the Elementary School level. Thus, the schools are not required to teach English to their students. However, some elementary schools still include English as one of the subjects and classroom teachers as an English teacher. Therefore, this research was aimed to figure out elementary school teachers’ perceptions on English teaching and school policy background in teaching English. This research used the descriptive method with questionnaires and interviews as the research instruments. The respondents of this research were 100 elementary schools and 11 principals. The result of the study revealed that most of the teachers assume that English is needed by elementary school students. The elementary school period is considered the best time to learn English, and they believe that English specialist teachers will be able to teach English better than the classroom teachers do. The data of interviews with 11 principals showed that 4 of 11 elementary schools still conducted English teaching and 7 schools did not implement English teaching because English is excluded from the 2013 Curriculum. All of the principals stated that the main problem of the implementation of English teaching at Elementary school was the availability of English specialist teachers.